Silicon carbide single crystal and method for producing same
The silicon carbide single crystals are prepared through polymerization reaction and silica shell deposition technology, which solves the problems of complex processes and high energy consumption in the prior art, and realizes an efficient and simple preparation method. The obtained silicon carbide single crystals have excellent mechanical and thermal properties.
Patent Information
- Application Number
- CN202411629090.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art when preparing high-performance silicon carbide single crystals, the process is complex, the energy consumption is high, and the carbonization conversion efficiency of silicon-containing polymers is low, which makes it easy to cause defects.
By polymerizing the silicone source, polymer monomer and initiator, a polymer containing silane groups is obtained, and a silicon dioxide shell layer is deposited on its surface to form a core-shell structure precursor, and then calcined to obtain a silicon carbide single crystal.
The preparation efficiency and process simplicity are achieved while maintaining the structural density and component purity, and the obtained silicon carbide single crystal has uniform size, dense structure, high compressive strength and excellent thermal conductivity.
Smart Images

Figure CN119593048A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon carbide single crystals, and in particular to a silicon carbide single crystal and a preparation method thereof. Background Art
[0002] Silicon carbide single crystal is an important structural ceramic material with excellent properties such as high temperature resistance, corrosion resistance, and wear resistance. It is widely used in aerospace, electronic power, mechanical manufacturing and other fields. At present, the common methods for preparing high-performance silicon carbide single crystals mainly include: using silane precursors to directly deposit silicon carbide single crystals through pyrolysis or chemical vapor deposition; or carbonizing silicon-containing polymer precursors at high temperatures to prepare silicon carbide single crystals. However, although pyrolysis or chemical vapor deposition methods can obtain high-purity silicon carbide single crystal materials, the process is complex and energy consumption is high; using silicon-containing polymer precursors as templates can prepare relatively dense silicon carbide single crystal materials, but the carbonization conversion efficiency of silicon-containing polymers is low and defects are prone to occur.
[0003] Therefore, there is a need for a method for preparing silicon carbide single crystals that can further improve preparation efficiency and process simplicity while maintaining high structural density and component purity. Summary of the invention
[0004] Based on this, it is necessary to provide a silicon carbide single crystal and a preparation method thereof to address the above problems. The preparation method provided by the present invention has the advantages of high preparation efficiency and simple process, which is conducive to the large-scale production of silicon carbide single crystals, and the prepared silicon carbide single crystals have uniform size, dense structure, high compressive strength, and excellent thermal conductivity, and can be widely used in the field of advanced structural materials.
[0005] The present invention provides a method for preparing a silicon carbide single crystal, comprising the following steps:
[0006] The organic silicon source, the polymer monomer and the initiator are polymerized to obtain a polymer containing a silane group;
[0007] Depositing silicon dioxide on the surface of the polymer containing silane groups to obtain a core-shell structure precursor;
[0008] The core-shell structure precursor is calcined to obtain a silicon carbide single crystal.
[0009] In one of the embodiments, the mass ratio of the organosilicon source to the polymer monomer and the initiator is (10-1000):(100-1):(100-0.1).
[0010] In one embodiment, the organic silicon source is selected from at least one of methyltriethoxysilane, octyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, phenyltrimethoxysilane and silane-containing polysiloxane;
[0011] And / or, the polymer monomer is selected from at least one of an acrylate monomer, a vinyl monomer and an epoxy resin monomer;
[0012] And / or, the initiator is selected from at least one of azobisisobutyronitrile, sodium dodecyl sulfate, benzoyl peroxide and ammonium persulfate.
[0013] In one embodiment, the polymerization reaction is carried out at a temperature of 60° C. to 120° C. and for a time of 4 h to 8 h.
[0014] In one of the embodiments, the mass ratio of the polymer containing silane groups to the silicon dioxide is 1:20 to 1000:1.
[0015] In one of the embodiments, the thickness of the silicon dioxide shell layer in the core-shell structure precursor is 8 nm to 800 nm.
[0016] In one embodiment, the silicon dioxide is deposited by a method selected from a sol-gel method, a chemical vapor deposition method or a physical vapor deposition method.
[0017] In one embodiment, when the sol-gel method is used to deposit silicon dioxide, the following steps are included: mixing the polymer containing silane groups with an organic silane compound, and adding an acid catalyst or a base catalyst to perform a hydrolysis condensation reaction to obtain a core-shell structure precursor.
[0018] In one of the embodiments, in the calcination step, the calcination temperature is 800° C. to 1800° C., the heating rate is 2° C. / min to 5° C. / min, and the holding time is 2 h to 10 h.
[0019] The present invention also provides a silicon carbide single crystal obtained by the preparation method as described above.
[0020] The above-mentioned method for preparing silicon carbide single crystals copolymerizes an organic silicon source with a polymer monomer through a free radical copolymerization reaction to obtain a polymer containing a silane group, thereby achieving uniform dispersion of silicon elements in the polymer, which is beneficial to improving the preparation efficiency and the quality of silicon carbide single crystal products. At the same time, a silicon dioxide shell is introduced on the surface of the polymer containing a silane group, which not only provides structural support for the growth of silicon carbide single crystals, but also helps to inhibit the entry of impurities, thereby further improving the product quality of the obtained silicon carbide single crystals. Compared with the existing polymer carbonization method, the preparation method provided by the present invention has higher preparation efficiency and simpler process, which is conducive to the large-scale production of silicon carbide single crystals, and the obtained silicon carbide single crystals have excellent properties such as uniform size, dense structure, high compressive strength, and good thermal conductivity, and can be widely used in the field of advanced structural materials.
[0021] Therefore, the preparation method of the present invention realizes fine control of the structure and performance of silicon carbide single crystals through dual designs at the molecular level and the microstructural level, improves the efficiency of silicon carbide single crystal preparation and product quality, and has good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a characterization result diagram of the silicon carbide single crystal obtained in Example 1 of the present invention, wherein: Figure 1 (a) is a TEM image of the silicon carbide single crystal obtained in Example 1 of the present invention, Figure 1 (b) is a HR-TEM image of the silicon carbide single crystal obtained in Example 1 of the present invention, Figure 1 (c) is a lattice fringe diagram of the silicon carbide single crystal obtained in Example 1 of the present invention, Figure 1 (d) is a selected area electron diffraction pattern of the silicon carbide single crystal obtained in Example 1 of the present invention;
[0024] Figure 2 The XRD diffraction pattern of the silicon carbide single crystal prepared in Example 1 of the present invention;
[0025] Figure 3 The XRD diffraction pattern of the material prepared in Comparative Example 1 of the present invention;
[0026] Figure 4 This is a TEM image of the material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0027] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0029] The method for preparing a silicon carbide single crystal provided by the present invention comprises the following steps:
[0030] S1, polymerizing an organosilicon source, a polymer monomer and an initiator to obtain a polymer containing a silane group;
[0031] S2, depositing silicon dioxide on the surface of the polymer containing silane groups to obtain a core-shell structure precursor;
[0032] S3, calcining the core-shell structure precursor to obtain a silicon carbide single crystal.
[0033] In step S1, under the action of an initiator, the organic silicon source and the polymer monomer undergo a free radical copolymerization reaction to obtain a polymer containing a silane group, thereby achieving uniform incorporation of silicon elements at the molecular level, laying the foundation for the subsequent efficient generation of silicon carbide single crystals, and is beneficial to improving the crystal size uniformity, structural density, compressive strength and thermal conductivity of the silicon carbide single crystals.
[0034] In one embodiment, the mass ratio of the organic silicon source to the polymer monomer and the initiator is (50-800):(30-10):(20-1), which is beneficial to further improve the uniformity of silicon incorporation in the polymer, to ensure the growth of silicon carbide single crystals, while avoiding the production of crystalline silicon dioxide, improving the purity of silicon carbide single crystals, and thereby improving the preparation efficiency of silicon carbide single crystals and the quality of silicon carbide single crystal products.
[0035] Preferably, the mass ratio of the organic silicon source to the polymer monomer and the initiator is (200-800):(80-20):(10-0.5).
[0036] In order to avoid the violent polymerization of the organic silicon source and the polymer monomer and to further improve the uniformity of the incorporation of silicon elements into the polymer, the polymerization reaction temperature is preferably 60° C. to 120° C. and the polymerization time is preferably 4 h to 8 h.
[0037] More preferably, the polymerization reaction temperature is 60°C to 80°C.
[0038] It should be noted that, in order to improve the mixing uniformity of the organosilicon source and the polymer monomer, the organosilicon source and the polymer monomer can be added to an organic solvent such as ethanol, mixed by stirring, shaking, etc., then heated under a protective atmosphere, and an initiator is added to carry out a free radical copolymerization reaction.
[0039] In one embodiment, the organosilicon source is at least one selected from an organosilane compound and a silane-containing polysiloxane.
[0040] Preferably, the organic silane compound is selected from at least one of methyltriethoxysilane, octyltriethoxysilane, tetramethoxysilane, tetraethoxysilane and phenyltrimethoxysilane.
[0041] In one embodiment, the polymer monomer is selected from at least one of an acrylate monomer, a vinyl monomer, and an epoxy resin monomer.
[0042] In one embodiment, the initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide, sodium dodecyl sulfate and ammonium persulfate.
[0043] In step S2, a dense silica shell layer is deposited on the surface of the polymer containing silane groups to obtain a core-shell structure precursor. On the one hand, the introduced silica shell layer can provide structural support for the growth of silicon carbide single crystals, effectively guarantee the generation of silicon carbide single crystals, and at the same time improve the purity and density of silicon carbide single crystals, thereby improving the compressive strength and thermal conductivity of silicon carbide single crystals; on the other hand, it effectively inhibits impurities from entering the interior of the polymer containing silane groups, further improving the purity and density of the product.
[0044] In one embodiment, the mass ratio of the polymer containing silane groups to the silicon dioxide is 1:10 to 800:1.
[0045] Preferably, the mass ratio of the polymer containing silane groups to the silicon dioxide is 1:10 to 200:1.
[0046] In one embodiment, the thickness of the silicon dioxide shell layer in the core-shell structure precursor is 8 nm to 800 nm, which is beneficial to improving the size uniformity, compressive strength and thermal conductivity of the prepared silicon carbide single crystal.
[0047] Preferably, the thickness of the silicon dioxide shell layer in the core-shell structure precursor is 20 nm to 500 nm.
[0048] More preferably, the thickness of the silicon dioxide shell layer in the core-shell structure precursor is 30 nm to 200 nm.
[0049] In one embodiment, the silicon dioxide is deposited by a method selected from a sol-gel method, a chemical vapor deposition method or a physical vapor deposition method.
[0050] It should be noted that the above-mentioned sol-gel method, chemical vapor deposition method and physical vapor deposition method are all conventional methods in the art, and the present invention has no special limitation thereto.
[0051] Specifically, when the sol-gel method is used to deposit silicon dioxide, the following steps are included: mixing the polymer containing silane groups with an organic silane compound, and adding an acid catalyst or a base catalyst to carry out a hydrolysis condensation reaction to obtain a core-shell structure precursor.
[0052] Preferably, the organic silane compound is selected from at least one of tetraethoxysilane, phenyltriethoxysilane and vinyltrimethoxysilane.
[0053] Preferably, the polymer containing silane groups is added to an ethanol / water solution and heated to 20°C to 40°C, and then the organosilane compound is added and mixed, and then an acid catalyst or a base catalyst is added to adjust the pH of the system to 2 to 3 or 9 to 11, so that the organosilane compound undergoes a hydrolysis condensation reaction.
[0054] It should be noted that the organosilane compound used in the sol-gel method to deposit silica can be the same as or different from the organosilicon source used in the preparation of the polymer containing silane groups; the above-mentioned acid catalyst and base catalyst are conventional catalysts in the field, and the present invention has no special restrictions on this.
[0055] In step S3, the core-shell structure precursor is calcined to cause a pyrolysis reaction of the core-shell structure precursor, and the silicon element and the carbon element react fully to generate a dense silicon carbide single crystal.
[0056] In one embodiment, in the calcination step, the calcination temperature is 800° C. to 1800° C., the heating rate is 2° C. / min to 5° C. / min, and the holding time is 2 h to 10 h. This is beneficial to promote the full reaction of silicon and carbon elements and improve the compressive strength and thermal conductivity of the silicon carbide single crystal.
[0057] It is understandable that in the calcination step, the core-shell structure precursor is calcined in a protective atmosphere to promote the crosslinking and conversion of silicon and carbon elements. The protective atmosphere is selected from nitrogen, argon, etc., and the present invention has no special limitation on this.
[0058] The present invention also provides a silicon carbide single crystal prepared by the preparation method as described above, the silicon carbide single crystal has high purity and has excellent properties such as uniform size, dense structure, high compressive strength, high compressive strength and good thermal conductivity, and can be widely used in the field of advanced structural materials.
[0059] The silicon carbide single crystal and its preparation method will be further described below by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0060] Example 1
[0061] 20 g of methyltriethoxysilane (MTES) and 80 g of methyl acrylate (MMA) were added to 200 g of ethanol solvent and stirred at 300 rpm / min. The reaction solution was then heated to 70°C under nitrogen protection. Subsequently, 0.1 g of azobisisobutyronitrile (AIBN) was added as an initiator and reacted for 6 hours. The obtained solution included a polymer containing silane groups. The solution was cooled to room temperature for standby use.
[0062] 20 g of the above solution was added to 200 g of a 25 wt% ethanol / water solution and stirred evenly, and then 10 g of tetraethoxysilane (TEOS) was added to make it evenly dispersed in the reaction system, and then a small amount of hydrochloric acid was added as an acidic catalyst to adjust the pH to about 3, and the reaction was carried out at 30° C. and 300 rpm / min for 4 hours to coat the surface of the polymer with a silica shell to obtain a core-shell structure precursor, wherein the mass ratio of the polymer containing silane groups to silica is 200:1, and the thickness of the silica shell is 67 nm.
[0063] The core-shell structure precursor was placed in a nitrogen atmosphere, heated to 1000° C. at a heating rate of 3° C. / min, and kept warm for 4 hours to obtain a silicon carbide single crystal material.
[0064] Example 2
[0065] 40 g of MTES and 80 g of MMA were added to 200 g of ethanol solvent and stirred at 300 rpm / min. The reaction solution was then heated to 70°C under nitrogen protection. Subsequently, 0.1 g of AIBN was added as an initiator and reacted for 6 hours. The resulting solution included a polymer containing silane groups. The solution was cooled to room temperature for later use.
[0066] 20 g of the above solution was added to 200 g of a 25 wt% ethanol / water solution and stirred evenly, and then 20 g of TEOS was added to make it evenly dispersed in the reaction system, and then a small amount of hydrochloric acid was added as an acidic catalyst to adjust the pH to about 3, and the whole reaction was allowed to react at 30° C. and 300 rpm / min for 4 hours, and a silica shell layer was coated on the surface of the polymer to obtain a core-shell structure precursor, wherein the mass ratio of the polymer containing silane groups to silica was 101:1, and the thickness of the silica shell layer was 85 nm.
[0067] The core-shell structure precursor was placed in a nitrogen atmosphere, heated to 1000° C. at a heating rate of 3° C. / min, and kept warm for 4 hours to obtain a silicon carbide single crystal material.
[0068] Example 3
[0069] 40 g of MTES and 80 g of MMA were added to 200 g of ethanol solvent and stirred at 300 rpm / min. The reaction solution was then heated to 70°C under nitrogen protection. Subsequently, 0.1 g of AIBN was added as an initiator and reacted for 6 hours. The resulting solution included a polymer containing silane groups. The solution was cooled to room temperature for later use.
[0070] 20 g of the above solution was added to 200 g of a 25 wt% ethanol / water solution and stirred evenly, and then 20 g of TEOS was added to make it evenly dispersed in the reaction system, and then a small amount of hydrochloric acid was added as an acidic catalyst to adjust the pH to about 3, and the whole reaction was allowed to react at 30° C. and 300 rpm / min for 4 hours, and a silica shell layer was coated on the surface of the polymer to obtain a core-shell structure precursor, wherein the mass ratio of the polymer containing silane groups to silica was 1:20, and the thickness of the silica shell layer was 456 nm.
[0071] The core-shell structure precursor was placed in an argon atmosphere, heated to 1000° C. at a heating rate of 3° C. / min, and kept warm for 4 hours to obtain a silicon carbide single crystal material.
[0072] Example 4
[0073] The difference between Example 4 and Example 3 is that the core-shell structure precursor is placed in an argon atmosphere, the temperature is increased to 1600° C. at a heating rate of 3° C. / min, and the temperature is kept for 4 hours to obtain a silicon carbide single crystal material.
[0074] Example 5
[0075] 20 g of phenyltrimethoxysilane and 80 g of styrene monomer were added to 200 g of ethanol solvent and stirred at 400 rpm / min. The reaction solution was then heated to 80°C under nitrogen protection. Subsequently, 0.1 g of AIBN was added as an initiator and reacted for 6 hours. The resulting solution included a polymer containing silane groups. The solution was cooled to room temperature for later use.
[0076] 20 g of the above solution was added to 200 g of a 25 wt% ethanol / water solution and stirred evenly, and then 20 g of TEOS was added to make it evenly dispersed in the reaction system, and then a small amount of hydrochloric acid was added as an acidic catalyst to adjust the pH to about 3, and the whole reaction was carried out at 40°C and 350 rpm / min for 4 hours, and a silica shell layer was coated on the surface of the polymer to obtain a core-shell structure precursor, wherein the mass ratio of the polymer containing silane groups to silica was 300:1, and the thickness of the silica shell layer was 57 nm.
[0077] The core-shell structure precursor was placed in a nitrogen atmosphere, heated to 1000° C. at a heating rate of 3° C. / min, and kept warm for 4 hours to obtain a silicon carbide single crystal material.
[0078] Example 6
[0079] 40 g of octyltriethoxysilane and 80 g of phenolic epoxy resin were added to 200 g of ethanol solvent and stirred at 300 rpm / min. The reaction solution was then heated to 80°C under nitrogen protection. Subsequently, 1 g of ammonium persulfate was added as an initiator and reacted for 6 hours. The resulting solution included a polymer containing silane groups. The solution was cooled to room temperature for later use.
[0080] First, 20g of a polymer containing a silane group is dissolved in 200 grams of a 25wt% ethanol / water solution and stirred at 300rpm / min in a stirrer to ensure that the polymer is evenly distributed. Then, 10g of TEOS is added to the solution and stirring is continued to achieve uniform dispersion in the reaction system. Subsequently, a small amount of hydrochloric acid is gradually added as an acidic catalyst to adjust the pH value of the solution to about 3 to promote the CVD reaction. Under the conditions of maintaining a constant temperature of 30°C and stirring at 300rpm / min, the mixed solution is reacted in a CVD reactor for 4 hours to achieve vapor deposition of silane groups on the surface of the polymer to obtain a core-shell structure precursor, wherein the mass ratio of the polymer containing a silane group to silica is 150:1, and the thickness of the silica shell is 78nm.
[0081] The core-shell structure precursor was placed in a nitrogen atmosphere, heated to 1000° C. at a heating rate of 3° C. / min, and kept warm for 4 hours to obtain a silicon carbide single crystal material.
[0082] Comparative Example 1
[0083] 40 g of MTES and 80 g of MMA were added to 200 g of ethanol solvent and stirred evenly at a speed of 300 rpm / min. The reaction solution was then heated to 70°C under nitrogen protection, and then 0.1 g of AIBN was added as an initiator to react for 6 hours and then cooled to room temperature. The mixture was washed with water and ethanol three times respectively, and the supernatant was removed by centrifugation. After drying in a vacuum drying oven at 60°C, a polymer containing silane groups was obtained.
[0084] The dried polymer precursor core-shell structure precursor was placed in an argon atmosphere, heated to 1600° C. at a heating rate of 3° C. / min, and kept warm for 4 hours to obtain the material.
[0085] Comparative Example 2
[0086] 100 g of methyl acrylate (MMA) was added to 200 g of ethanol solvent and stirred at 300 rpm / min. The reaction solution was then heated to 70°C under nitrogen protection. Subsequently, 0.1 g of azobisisobutyronitrile (AIBN) was added as an initiator and reacted for 6 hours. The obtained solution was cooled to room temperature for standby use.
[0087] 20 g of the above solution was added to 200 g of a 25 wt% ethanol / water solution and stirred evenly, and then 10 g of TEOS was added to make it evenly dispersed in the reaction system, and then a small amount of hydrochloric acid was added as an acidic catalyst to adjust the pH to about 3, and the reaction was carried out at 30° C. and 300 rpm / min for 4 hours to coat the surface of the polymer with a silica shell to obtain a core-shell structure precursor, wherein the mass ratio of the polymer containing silane groups to silica is 500:1, and the thickness of the silica shell is 15 nm.
[0088] The core-shell structure precursor was placed in a nitrogen atmosphere, heated to 1000° C. at a heating rate of 3° C. / min, and kept warm for 4 hours to obtain a silicon carbide single crystal material.
[0089] The performance of the materials prepared in all the embodiments and comparative examples was characterized. The morphology and size of the silicon carbide single crystal were observed using a scanning electron microscope, the compressive strength of the silicon carbide single crystal was tested using a compression testing machine, and the thermal conductivity of the silicon carbide single crystal was tested using a thermocouple tester. The test results are shown in Table 1.
[0090] Table 1
[0091]
[0092]
[0093] The silicon carbide single crystal material prepared in Example 1 was characterized by observing the morphology of the silicon carbide single crystal material using a transmission electron microscope, observing the lattice distribution of the silicon carbide single crystal material using a high-resolution transmission electron microscope, testing the crystallinity of the silicon carbide single crystal material using X-ray powder diffraction, and observing the crystal plane information and crystallization of the silicon carbide single crystal material using a selected area electron diffraction spectrum. Figure 1 As shown, this is a characterization result diagram of the silicon carbide single crystal material obtained in Example 1. Figure 1 From the TEM image (a), it can be seen that the surface of the silicon carbide single crystal is relatively dense, the particle size distribution is relatively uniform, and the average grain size is about 200nm. Figure 1 (b) HR-TEM image shows that the prepared silicon carbide single crystal material has obvious lattice fringes, indicating that it has good crystallinity. Figure 1 (c) The enlarged lattice fringe diagram shows that the silicon carbide single crystal obtained in Example 1 has regularly arranged lattice fringes, and the interplanar spacing is 0.16 nm, indicating that the silicon carbide single crystal has a (200) oriented crystal plane. Figure 1 (d) is the selected area electron diffraction pattern of the silicon carbide single crystal material prepared in Example 1. It can be seen that the silicon carbide single crystal material prepared in Example 1 has silicon carbide crystal planes. Figure 2 The XRD pattern of the silicon carbide single crystal material prepared in Example 1 is shown in Figure 2. It can be seen that it meets the standard diffraction peaks of silicon carbide single crystals, indicating that high-purity silicon carbide single crystals are prepared in Example 1. The XRD diffraction pattern of the material prepared in Comparative Example 1 is shown in Figure 2. Figure 3 As shown, it can be seen that the main diffraction peak is the standard diffraction peak of crystalline silicon dioxide, indicating that the material prepared in Comparative Example 1 is mainly crystalline silicon dioxide, rather than silicon carbide single crystal, and according to Figure 4 It can be seen that the size distribution of the material prepared in Comparative Example 1 is uneven.
[0094] Combined with the results in Table 1, Example 1 and Example 2 compare the relationship between the doping amount of silane groups in the free radical polymerization reaction, the thickness of the silicon dioxide shell layer, and the particle size, compressive strength and thermal conductivity of the silicon carbide single crystal obtained after sintering. The results show that increasing the amount of silane groups and the thickness of the silicon dioxide shell layer in the free radical polymerization reaction can significantly improve the particle size, compressive strength and thermal conductivity of the silicon carbide single crystal, indicating that increasing the doping amount of silane groups can promote the full crosslinking between them and the polymer monomer structure and improve the conversion; By comparing Example 2 and Example 3, it can be seen that while keeping the doping amount of silane groups and the reaction conditions consistent, the inert gas used in the sintering process is replaced from nitrogen to argon. Within the same sintering time, the thermal conductivity of the silicon carbide single crystal sintered in an argon atmosphere is increased by 43%, and the compressive strength is increased by 28.5%. This is because argon has a higher thermal conductivity than nitrogen, which enhances the full crosslinking and conversion between carbon and silicon elements; By comparing Example 3 and Example 4, It is known that, while keeping the silane group, the amount of polymer and the sintering time the same, increasing the sintering temperature can significantly improve the compressive strength and thermal conductivity of the silicon carbide single crystal; By comparing Example 4 with Comparative Example 1, it can be seen that when the surface of the polymer containing the silane group is not coated with a silica shell layer, simply calcining the precursor will not cause it to be completely converted, and the purity of the obtained silicon carbide single crystal is not high, and its compressive strength and thermal conductivity are both low. This is because the crystal growth of the silicon carbide single crystal requires a certain support. The introduction of the silica shell layer in each embodiment provides a strong support for the crystal growth of the silicon carbide single crystal, and also inhibits impurities from entering the interior of the polymer containing the silane group, thereby improving the purity and density of the product; By comparing Example 1 with Comparative Example 2, it can be seen that since the polymer is not doped with silicon element, and the silica of the coating layer is not chemically combined with the polymer, and an ordered structure is not formed, it is impossible to guide the carbon and silicon atoms to arrange in the lattice of the single crystal, so a single crystal structure cannot be formed. Therefore, Comparative Example 2 cannot generate a silicon carbide single crystal.
[0095] In summary, the embodiments of the present invention successfully produce high-purity silicon carbide single crystals with uniform size, dense structure, high compressive strength, excellent thermal conductivity, etc., and can be widely used in the field of advanced structural materials.
[0096] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0097] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a silicon carbide single crystal, characterized in that: The preparation method comprises the following steps: The organic silicon source, the polymer monomer and the initiator are polymerized to obtain a polymer containing a silane group; Depositing silicon dioxide on the surface of the polymer containing silane groups to obtain a core-shell structure precursor; The core-shell structure precursor is calcined to obtain a silicon carbide single crystal.
2. The method for preparing a silicon carbide single crystal according to claim 1, characterized in that: The mass ratio of the organic silicon source to the polymer monomer and the initiator is (10-1000):(100-1):(100-0.1).
3. The method for preparing a silicon carbide single crystal according to claim 1 or 2, characterized in that: The organic silicon source is selected from at least one of methyltriethoxysilane, octyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, phenyltrimethoxysilane and silane-containing polysiloxane; And / or, the polymer monomer is selected from at least one of an acrylate monomer, a vinyl monomer and an epoxy resin monomer; And / or, the initiator is selected from at least one of azobisisobutyronitrile, sodium dodecyl sulfate, benzoyl peroxide and ammonium persulfate.
4. The method for preparing a silicon carbide single crystal according to claim 1, characterized in that: The polymerization reaction temperature is 60° C. to 120° C., and the reaction time is 4 h to 8 h.
5. The method for preparing a silicon carbide single crystal according to claim 1, characterized in that: The mass ratio of the polymer containing silane groups to the silicon dioxide is 1:20 to 1000:
1.
6. The method for preparing a silicon carbide single crystal according to claim 1, characterized in that: The thickness of the silicon dioxide shell layer in the core-shell structure precursor is 8nm to 800nm.
7. The method for preparing a silicon carbide single crystal according to claim 1, characterized in that: The silicon dioxide is deposited by a method selected from a sol-gel method, a chemical vapor deposition method or a physical vapor deposition method.
8. The method for preparing a silicon carbide single crystal according to claim 7, characterized in that: When the sol-gel method is used to deposit silicon dioxide, the following steps are included: mixing the polymer containing silane groups with an organic silane compound, and adding an acid catalyst or a base catalyst to carry out a hydrolysis condensation reaction to obtain a core-shell structure precursor.
9. The method for preparing a silicon carbide single crystal according to claim 1, characterized in that: In the calcination step, the calcination temperature is 800° C. to 1800° C., the heating rate is 2° C. / min to 5° C. / min, and the insulation time is 2 h to 10 h.
10. A silicon carbide single crystal obtained by the preparation method according to any one of claims 1 to 9.